THE INTEGRATION OF RELIGION, POLITICS, ECONOMY AND TECHNOLOGY IN INDONESIA - Hulwati Hulwati; Slamet Mujiono; Nelmawarni Nelmawarni; Ahmad Wira (Universitas Islam Negeri Imam Bonjol Padang, 2020)
Science and technology development is an indication of human civilization progress which has the merit of a religious point of view. Based on anthology and epistemology, the development itself has shown amazing result, however based on axiology, the development itself requires great attention. In this case, there are four phenomenon arise in society related with the integration of religion, economy, and technology; namely i). Religion, economy, and technology are separating; ii) The occurrence of confrontation among religion, economy, and technology; iii) There is a dialogical relationship, and iv) The occurrence of integration. All of the four phenomenon are the axiology basic of human civilization progress. Implementing the axiology in society depends on the integration of religion, politics, economy, and technology with a reciprocal relationship to build benefit, justice, and democracy in a country, particularly in Indonesia. Nowadays in Indonesia, the relationship among religion, economy and technology is at the political policy variant level. Therefore, this research hinges on the integration of religion, politics, economy, and technology in Indonesia.